Sustainability and Innovation of the Pancasila and Citizenship Education Curriculum for Elementary, Secondary, and Higher Education in Indonesia - Sari, Windy Dian; Sarnoto, Ahmad Zain (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the Pancasila and Citizenship education curriculum for elementary, secondary, and higher education in Indonesia. This is because the Pancasila education curriculum is starting to weaken amidst the current tide of globalism that brings various other world ideologies that challenge the Pancasila ideology. This study uses a qualitative approach through the use of library research tools. Because the method used is a library method, this study relies on primary sources from study materials from previous researchers or literature reviews. Content data analysis is a data collection approach that includes documentation and data analysis. The approach used is curriculum management. The theories used to analyze the data are the theory of curriculum sustainability and the theory of curriculum innovation. The findings of this study indicate: first, the Sustainability of the Pancasila and Citizenship Education Curriculum. Second, the Sustainability of the Pancasila and Citizenship Education Curriculum. Third, Innovation of the Pancasila and Citizenship Education Curriculum. Fourth, Challenges in Implementing the Pancasila and Civics Education Curriculum. Fifth, Opportunities for Developing the Pancasila and Civics Education Curriculum. The findings of this study contribute to enriching the discourse on the sustainability and innovation of the Pancasila and Civics Education curriculum.